Captivity affects diversity, abundance, and functional pathways of gut microbiota in the northern grass lizard Takydromus septentrionalis. Issue 9 (14th July 2020) - Zhou, Jin; Zhao, Yu‐Tian; Dai, Ying‐Yu; Jiang, Yi‐Jin; Lin, Long‐Hui; Li, Hong; Li, Peng; Qu, Yan‐Fu; Ji, Xiang
Abstract: Animals in captivity undergo a range of environmental changes from wild animals. An increasing number of studies show that captivity significantly affects the abundance and community structure of gut microbiota. The northern grass lizard ( Takydromus septentrionalis ) is an extensively studied lacertid lizard and has a distributional range covering the central and southeastern parts of China. Nonetheless, little is known about the gut microbiota of this species, which may play a certain role in nutrient and energy metabolism as well as immune homeostasis. Here, we examined the differences in the gut microbiota between two groups (wild and captive) of lizards through 16S rRNA sequencing using the Illumina HiSeq platform. The results demonstrated that the dominant microbial components in both groups consisted of Proteobacteria, Firmicutes, and Tenericutes. The two groups did not differ in the abundance of these three phyla. Citrobacter was the most dominant genus in wild lizards, while Morganella was the most dominant genus in captive lizards. Moreover, gene function predictions showed that genes at the KEGG pathway levels2 were more abundant in wild lizards than in captive lizards but, at the KEGG pathway levels1, the differences in gene abundances between wild and captive lizards were not significant. In summary, captivity exerted a significant impact on the gut microbial community structure and diversity in T .  septentrionalis, and future work could usefully investigate the causes of these changes using a comparative approach. Abstract : The dominant taxon with the abundance of >1% in gut microbiota was compared between wild and captive northern grass lizards ( Takydromus septentrionalis ). Significant differences were found between the two groups of lizards at all levels from class down to genus. Our results provide an inference that captivity can affect the species diversity and abundance of gut microbiota in lizards.